Development of an electrochemical aptasensor based on nanomaterials-modified electrode for the detection of zearalenone and cross-reactivity towards masked zearalenone - Azri, Farah Asilah (2021)
Zearalenone (ZEA) is a phytohormone that is primarily an estrogenic fungal metabolite. ZEA exhibits a genotoxic potential in vitro and in vivo, and therefore, the determination of ZEA in food and feedstuffs is of great importance for food safety monitoring. Masked ZEA is derivative generated through chemical transformations which catalysed by plant enzymes and commonly undetectable by conventional analytical techniques. Hence, the aim of this study is to develop a novel, sensitive, and direct aptamer-based electrochemical biosensor based on a graphene nanoplatelets-chitosan/gold nanoparticle (GNP-CS/AuNPs) modified electrode using a thiolated aptamer with methylene blue (MB) as a redox mediator, for detection of ZEA and masked ZEA. In this study, two different detection formats which are indirect competitive and direct have been employed on gold and carbon electrode, respectively. The binding affinity and selectivity of the selected aptamer were first studied and proved that the hypothesis of possible cross-reactivity towards masked ZEA, including α-zearalenol (α-ZEL), β -zearalenol (β-ZEL) and zearalenone-14-glucoside (ZEA-14-Glc) was correct. The dissociation constant (Kd) of the aptamer was obtained at 13.42 ± 2.1 nM and the conformational characterisation using circular dichroism (CD) resulted in a change in the molecular ellipticity. The indirect competitive aptasensor showed an excellent dynamic range in between 0.01 to 1000 ng/mL, with a detection limit of 0.017 ng/mL. Besides, the cross-reactivity analysis proved a high degree of cross-reaction towards the masked ZEA. The sensitivity of aptamer was further improved by truncation. Fifteen truncation variants were evaluated by computational docking for binding simulation. Aptamer Z31N had the lowest Vina score of -7.8 kcal/mol, with the most significant number of intermolecular interactions and Kd of Z31N aptamer was calculated as 11.77 ± 1.44 nM. The sensing platform was then fabricated by modifying the SPCE with GNP-CS mixture and AuNPs. The AuNPs were synthesised using the extract of Etlingera elatior and the results showed that the AuNPs with an average size of 31 nm and zeta potential of -32.0 mV were comparable with the citrate-mediated AuNPs. The modified SPCE with 4 mg/mL of GNP in 0.1% CS and 20 μL of AuNPs showed an excellent electrical conductivity and stability. Under optimised conditions, the detection of ZEA was based on the redox probe of MB at the 3’ end of the aptamer. Good response of the direct aptasensor was obtained within the range of 0.001 to 100 ng/mL with a detection limit of 0.14 pg/mL, which was lower than the indirect competitive aptasensor. This result proved that the truncation of the aptamer was efficient in enhancing the sensitivity of the aptamer as biosensing material. Moreover, the analysis in grain maize sample also showed good recovery of between 96 - 122%. It can be concluded that the developed aptasensor can be used for a total detection of ZEA in the sample as a high degree of cross-reactivity can be observed in both formats which could be advantages for mycotoxin screening.